Nghiên cứu quá trình chuyển hóa asen và một số thành phần cơ bản trong nước ngầm trên thiết bị mô phỏng môi trường yếm khí tự nhiên - Cam, Bùi Duy; Côn, Trần Hồng; Dung, Nguyễn Thị Kim (Vietnam Journal of Chemistry, 2012)
In this work, the biochemical reduction of minerals containing iron, manganese and arsenate releasing arsenic, iron and manganese to water environment in anerobic conditions was investigated on the equipment imitated reductive process in underground equifer. The results showed close relationship between decrease of organic substances and desolved oxygen concentration with logical changing of arsenic, manganese, iron, sulfate, nitrate, phosphate, ammonia and H+ concentration in water and solid phases as well as transfering of their existing forms. The results of the work contributed to bring out the polluting mechanism of arsenic, manganese and other toxic substances in several groundwater resources.